Correction of conditions caused by herniated discs of the lumbar spine, on the example of using the thermotherapy stimulator massager - A. A. Mukhina; T. V. Marfina; T. V. Konchugova; L. G. Agasarov (Лечащий Врач, 2025)
Background. Compression of the lumbar or first crural roots of the spinal nerves by altered disc components is the basis of radiculopathies manifested by back pain, movement and sensory disorders. The spondyloarthrosis often observed in this case accompanies not only the elderly, but is also observed in 25-30 year olds. Here, congenital anomalies, vertebral instability, spondylolisthesis and spondylolysis, inadequate distribution of loads on the spinal compartments and, finally, degenerative-dystrophic changes themselves are considered as causes. The latest revision of clinical recommendations confirms the expediency of using non-drug methods of treatment against the background of drug correction. In particular, in order to enhance analgesic, anti-inflammatory, anti-edema and myorelaxing effects, methods of physiotherapy, reflexology, massage, physical therapy and balneotherapy are used.Results. The paper presents the features of clinical manifestations of herniated discs of the lumbosacral spine and options for correcting the resulting conditions. Among the techniques of non-drug therapy used for a given purpose, the methods of physiotherapy, reflexology, massage and therapeutic exercise are distinguished. Here, for obvious reasons, preference is given to equipment that includes various technologies of influence. One of these devices are massagers that combines the therapeutic possibilities of massage, electrical stimulation, thermotherapy and traction effects. In this regard, a separate part of the work is devoted to the detailing of these approaches, with the clarification of mechanisms and their effectiveness. At the same time, a series of his own works confirmed the effectiveness of the noted therapeutic approaches for "back pain", used even as a monomethod. In this case, the use of a combined technique, characteristic of this type of massager, can even cause potentiation of effects in the correction of conditions associated with herniated discs of the lumbosacral spine.